2018
DOI: 10.1002/xrs.2953
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis applied to particle‐induced X‐ray emission mapping

Abstract: The use of particle‐induced X‐ray emission (PIXE) for elemental speciation and quantification has gained new attention thanks to mapping capabilities. Microprobes are able to raster a proton beam and produce elemental maps on the micrometre scale. Moreover, recent developments of in‐air PIXE instrumentation have enabled the acquisition of large area elemental maps. However, the amount of data produced is very large, and the data processing is not trivial. In this paper, we propose the use of multivariate analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The routines and the cascade of algorithms applied to process PIXE data on mappings are presented in [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The routines and the cascade of algorithms applied to process PIXE data on mappings are presented in [9].…”
Section: Resultsmentioning
confidence: 99%
“…Summing the similar pixels as determined by a clustering algorithm increases statistics and improves detection limits. It also enables the identification of patterns in the recorded spectra, enabling the discovery of the correlation between elements along the mapped area and revealing nuances hardly observed by the naked eye [9]. A similar implementation can be found elsewhere [10].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Such an amount of memory could easily handle the 393 216 × 669 elements of the dataset, but the use of a training sets enables the analysis to be done in any conventional PC, and it has been shown to be effective for multivariate analysis of ToF-SIMS imaging data, in which neighbor pixels are highly correlated. Furthermore, with reduced subsets, the total processing time is conveniently reduced to a few seconds for the dataset presented in this paper. Determination of number of NMF components by contrast analysis: NMF is performed several times for the subsampled dataset with a varying number of components. For each result, obtained with k components, the contrast G k of matrix W was calculated accordingly to the definition given by Silva et al: where w i are the columns of matrix W , as shown in Figure . The highest k that still presents a significant increment in contrast G k is considered the ideal number of components that contains relevant information on the dataset. NMF of the subsampled dataset.…”
Section: Discussionmentioning
confidence: 99%
“…For each result, obtained with k components, the contrast G k of matrix W was calculated accordingly to the definition by Silva et. al 20 :…”
Section: IIImentioning
confidence: 99%